1986
DOI: 10.1083/jcb.102.2.500
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the epidermal growth factor (EGF) receptor within the endosome of EGF-stimulated epidermoid carcinoma (A431) cells.

Abstract: Abstract. We have followed the internalization pathway of both epidermal growth factor (EGF) and its receptor in human epidermoid carcinoma (A431) cells. Using EGF conjugated with horseradish peroxidase and anti-receptor monoclonal antibodies (TL5 and EGFR 1) coupled either directly or indirectly to colloidal gold we have identified an extensive elaboration of endosomal compartments, consisting of a peripheral branching network of tubular cisternae connected to vacuolar elements that contain small vesicles and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
85
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(90 citation statements)
references
References 37 publications
3
85
0
Order By: Relevance
“…Hence, EGF receptor down-regulation likely depends on several discrete sorting events activated during MVE maturation. Because ligandoccupied EGF receptors also accumulate in the internal vesicles of MVEs en route to lysosomes (Miller et al, 1986), we hypothesize that E3-13.7 has usurped a mechanism normally used during ligand-induced receptor down-regulation. Our model predicts that although some EGF receptor lysosomal sorting signals, including the leucine signal usurped by E3-13.7, may be activated by ligand-induced oligomerization, others acting distally may function in the context of monomers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, EGF receptor down-regulation likely depends on several discrete sorting events activated during MVE maturation. Because ligandoccupied EGF receptors also accumulate in the internal vesicles of MVEs en route to lysosomes (Miller et al, 1986), we hypothesize that E3-13.7 has usurped a mechanism normally used during ligand-induced receptor down-regulation. Our model predicts that although some EGF receptor lysosomal sorting signals, including the leucine signal usurped by E3-13.7, may be activated by ligand-induced oligomerization, others acting distally may function in the context of monomers.…”
Section: Discussionmentioning
confidence: 99%
“…The transferrin receptor, for example, is found on the limiting membrane of relatively immature MVEs (Hopkins, 1983), the CI-M6PR is enriched in MVEs with an intermediate degree of maturation (Hirst et al, 1998), and Lamp I is found predominantly in mature MVEs (van Deurs et al, 1993). In addition, selected cargo, including ligand-occupied EGF receptors (Miller et al, 1986), is sequestered in internal vesicles. Hence, EGF receptor down-regulation likely depends on several discrete sorting events activated during MVE maturation.…”
Section: Discussionmentioning
confidence: 99%
“…2). EGF and EGFR begin to accumulate in the intralumenal membranes of MVB that are located in the perinuclear area of the cell after 15-20 min of EGF-induced endocytosis [80,81,88,89]. Serial sectioning electron microscopy demonstrated that internal membranes of MVB represent vesicles that are not connected to the limiting membrane [90].…”
Section: Post-endocytic Trafficking Of Egfr Pathways Through Endosomesmentioning
confidence: 99%
“…Clathrin-coated vesicles containing EGF-receptor complexes rapidly release their coat and fuse with early endosomes, compartments of a heterogeneous morphology consisting of vesicular and tubular membranes and located at the periphery of the cell [78][79][80][81] (Fig. 2).…”
Section: Post-endocytic Trafficking Of Egfr Pathways Through Endosomesmentioning
confidence: 99%
“…Anti-plOO and synthetic EGF (with the addition of four extra lysine residues on the carboxyl terminus) were conjugated to horseradish peroxidase using SPDP (Sigma Chemical) as described previously (Hopkins and Trowbridge, 1983;Miller et al, 1986). a-2 M/HRP was prepared as described previously by Hopkins et al (1994).…”
Section: Electron Microscopymentioning
confidence: 99%